Meningkatkan Hasil Belajar Bahasa Indonesia Melalui Metode Pembelajaran Resitasi Pada Siswa Kelas III di SDN 2 Totoharjo - Widiyanti, Danisa; Ariyanto , Bambang; Nurkaif (SM Institute, 2025)
ABSTRACT This research aims to determine the increase in learning achievement by applying the recitation learning method in Indonesian language subjects for class III at SD Negeri 2 Toto Harjo. This is caused by the low learning achievement of students in Indonesian language subjects for class III at SD Negeri 2 Toto Harjo, which is caused by the lack of use of media or methods in the learning process. The research employs the Classroom Action Research (CAR) approach, conducted in two cycles, with each cycle consisting of two sessions. The study involves 16 third grade students as participants. Data is gathered through observation sheets, tests, interviews, and documentation. Data analysis is conducted using both quantitative and qualitative methods. The findings indicate that in the pretest, 37.5% of students achieved proficiency, and this increased by 12% in the subsequent assessment. The learning achievement level in the first cycle reached 50%. In the second cycle, there was a significant improvement of 33.3%, with a proficiency rate of 81.25%. Based on these findings, it can be concluded that the implementation of the recitation method effectively enhances the learning outcomes of third grade students in Indonesian language at SD Negeri 2 Toto Harjo. Keywords : Learning outcomes; Indonesian language; recitation learning method